An interfacial damage-plastic model for the simulation of masonry structures under monotonic and cyclic loadings. (August 2022) - Nie, Yu; Sheikh, Abdul; Visintin, Phillip; Griffith, Michael
Highlights: A damage plasticity interface model is developed for simulate masonry structures. The development of model is based on physical characteristics of mortar joints. The interface model is implemented with a finite element modelling framework. Masonry structures under monotonic and cyclic loading are simulated. Effective stress based formulation improved numerical efficiency and robustness. Abstract: A damage plasticity based interface constitutive model for simulating complex mixed behaviour of masonry joints is proposed in this paper. To improve the computational efficiency and robustness of the interface model, a novel modelling strategy is adopted to algorithmically decouple the damage and plastic deformations, which are treated separately in two stages. This approach helps to simulate elastic-perfectly-plastic behaviour in effective stress space and provides a non-evolving yield surface in the first stage which significantly improves the convergence of stress return mapping. In the second stage, a separate function is employed to model the evolution of damage used to quantify stress softening. The interface model is implemented within a finite element code used to analyse masonry structures of different scales/sizes under monotonic and cyclic loads. The experimental validation of the simulated results demonstrates good performance of the model in terms of accuracy and robustness. Moreover, the effects of different parameters on the model performance are investigated. One of the key parameters is the degradation of dilation angle incorporated through an energy based evolution function, which is observed to have importance in improving physical response and numerical performance.